Epileptic Seizures Induced by a Spontaneous Carotid Cavernous Fistula - Çelik, Güner Koyuncu (Case Rep Med, 2016)
A 79-year-old woman was admitted to our emergency department with complaints of fainting and loss of consciousness three times during the past month. She was diagnosed with epilepsy and started to be treated with antiepileptic drug. Physical examination showed, in the left eye, chemosis, limited eye movements in all directions, and minimal exophthalmos as unexisting symptoms on admission developed on the sixth day. Orbital magnetic resonance imaging (MRI) and digital subtraction angiography (DSA) imaging revealed a carotid cavernous fistula (CCF). Epileptic attacks and ophthalmic findings previously present but diagnosed during our examinations were determined to ameliorate completely after performing the coil embolization. Based on literature, we present the first case with nontraumatic CCF manifesting with epileptic seizures and intermittent eye symptoms in the present report.